Diagnosing type 2 diabetes using Hemoglobin A1c: a systematic review and meta-analysis of the diagnostic cutpoint based on microvascular complications - Alexandra E. Butler (6189536) (2020)
Aims Diabetic microvascular complications of retinopathy, nephropathy and neuropathy may occur at hemoglobin A1c levels (HbA1c) below the 6.5% (48 mmol/mol) diagnostic threshold. Our objective was to assess the validity of the HbA1c diagnostic cutpoint of 6.5% based upon published evidence of the prevalence of retinopathy, nephropathy and neuropathy as markers of diabetes. Methods Data Sources PubMed, Embase, Cochrane, Scopus and CINAHL from 1990-March 2019, grey literature sources. Study Selection All studies reported after 1990 (to ensure standardized HbA1c values) where HbA1c levels were presented in relation to prevalence of retinopathy, nephropathy or neuropathy in subjects not known to have diabetes. Data Extraction Studies were screened independently, data abstracted, and risk of bias appraised. Data Synthesis Data were synthesized using HbA1c categories of < 6.0% (< 42 mmol/mol), 6.0–6.4% (42–47 mmol/mol) and ≥ 6.5% (≥ 48 mmol/mol). Random-effects meta-analyses were conducted for retinopathy, nephropathy and neuropathy prevalence stratified by HbA1c categories. Random-effects multivariable meta-regression was conducted to identify predictors of retinopathy prevalence and sources of between-study heterogeneity. Results Pooled mean prevalence was: 4.0%(95% CI: 3.2–5.0%) for retinopathy, 10.5% (95% CI: 4.0–19.5%) for nephropathy, 2.5% (95% CI: 1.1–4.3%) for neuropathy. Mean prevalence when stratified for HbA1c < 6.0%, 6.0–6.4% and ≥ 6.5% was: retinopathy: 3.4% (95% CI: 1.8–5.4%), 2.3% (95% CI: 1.6–3.2%) and 7.8%(95% CI: 5.7–10.3%); nephropathy: 7.1% (95% CI: 1.7–15.9%), 9.6% (95% CI: 0.8–26.4%) and 17.1% (95% CI: 1.0–46.9%); neuropathy: 2.1% (95% CI: 0.0–6.8%), 3.4% (95% CI: 0.0–11.6%) and 2.8% (95% CI: 0.0–12.8%). Multivariable meta-regression showed HbA1c ≥ 6.5% (OR: 4.05; 95% CI: 1.92–8.57%), age > 55 (OR: 3.23; 95% CI 1.81–5.77), and African-American race (OR: 10.73; 95% CI: 4.34–26.55), to be associated with higher retinopathy prevalence. Marked heterogeneity in prevalence estimates was found across all meta-analyses (Cochran’s Q-statistic p < 0.0001). Conclusions The prevalence of nephropathy and moderate retinopathy was increased in subjects with HbA1c values ≥ 6.5% confirming the high specificity of this value for diagnosing T2DM; however, at HbA1c < 6.5% retinopathy increased at age > 55 years and, most strikingly, in African-Americans, suggesting there may be excess microvascular complication prevalence (particularly nephropathy) in individuals below the diabetes diagnostic threshold. Other Information Published in: Acta Diabetologica License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00592-020-01606-5